Pelatihan dan Pengembangan Keterampilan Sablon Bagi Pemuda di Desa Cibatu untuk Meningkatkan Keterampilan Ekonomis - Rian Ramadani; Etty Zuliawati Zed; M Adi Fazryan; Ahmad Najmudin (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
Economic independence is an important factor in improving community welfare, especially for youth in rural areas. Cibatu village, which has abundant human resource potential, faces challenges in the form of low youth access to skills that can be used as a source of income. This screen printing training and development program aims to increase the economic independence of Cibatu village youth by providing practical skills in the field of screen printing on textile media. The program implementation method includes theoretical and practical screen printing training, starting from the screen printing process to final production. The results of this training show an increase in participants' skills and higher motivation to start a screen printing business independently. Thus, this screen printing training and development is one of the strategic solutions in encouraging the economic independence of youth in Cibatu Village, which in turn contributes to improving community welfare